CREATIVE PROCESS OF CONTEMPORARY DANCE GEOMETRY: A CHOREOGRAPHIC WORK WITH A SOCIAL PSYCHOLOGICAL APPROACH - Venny Rosalina; Fabio Yuda (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2022)
This paper discusses the process of creating Geometry, a dance works by using a psychological approach to express the idea of the Minangkabau body in contemporary dance practice. Geometry dance works as a real picture of the behavior, thoughts, appreciation of human characters through the description of body dialogue and unique experiences as character expressions in dance works. This study resulted in a description of the creative process of contemporary dance creation based on the application of a psychological approach by describing creative values, appreciation values and behavioral values in a geometric creation. The audience's reflection becomes the impetus to feel the sensations of contemporary dancers' bodies. Basik Minang Kabau uses geometry as a critical reflection on the development of contemporary dance in West Sumatra as a form of the body of the Minangkabau tradition towards a contemporary body. Keywords: Geometry; psychology; Audience Reflection; choreography; creative processPROSES KREATIF TARI KONTEMPORER GEOMETRI: SEBUAH KARYA KOREOGRAFI DENGAN PENDEKATAN PSIKOLOGI SOSIAL  AbstrakTulisan ini membahas tentang sebuah proses kreatif dalam penciptaan tari kontemporer berjudul Geometri dengan menggunakan pendekatan psikologi sosial. Koreografi tersebut disusun untuk mengungkapkan gagasan tentang ketubuhan Minangkabau dalam  praktik tari kontemporer. Karya tari Geometri erupakan gambaran nyata dari perilaku, pemikiran, penghayatan karakter manusia melalui penjabaran dialog tubuh dan pengalaman unik sebagai ekspresi karakter dalam karya tari. Penelitian ini mengahasilkan sebuah uraian proses kreatif penciptaan tari kontemporer yang berbasis pada penerapan pendekatan psikologi dengan menjabarkan nilai-nilai kreatif, nilai penghayatan dan nilai bersikap dalam sebuah penciptaan geometri. Refleksi penonton menjadi dorongan untuk merasakan sensasi ketubuhan penari kontemporer. Basik minang kabau menjadikan karya geometri sebagai refleksi kritis terhadap perkembangan tari kontemporer di Sumatera Barat sebagai wujud tubuh tradisi minangkabau menuju tubuh kontemporer. Kata Kunci: Geometri; psikologi sosial, refleksi penonton; koreografi; proses kreatif